Integrated of fish and vegetable waste from fresh market to generate alternative energy - Shafura, Abidi (2010)
At the fresh market, fruit and vegetable markets produce a large amount of waste each year and its disposal need a lot of cost. This waste can be use to products of higher value that have a place on the market. The demand for energy is expected to increase worldwide over the next 24 years in the developing countries. Energy has always played an important role in human and economic development in societies. Microbial Fuel Cell (MFC) technology represents a new form of renewable energy by generate electricity. This technology can use bacterium already present in wastewater as catalysts. This study investigates the potential of Solanum Lycopersicum (tomatoes), Brassica Oleracea (cabbage), Cucumis Sativus (cucumber) , Clarias Batrachus (Catfish) and Pengasus Sutchi (Shark Catfish) wastes as substrate used in MFC to generate alternative energy. This study also determines the factor of surface area of electrode that will affect the voltage of the NEC. The differences composition of integrated of fish and vegetable waste was used for this study to determine and classify energy level base on composition wastes. The vegetable and fish waste was collected from Pasar Besar Kuantan and Pasar D g ro g Kemunting, That inte grated waste was done the kuncitjç pr w for 3 months. The percentage of 50% fish and 50% of vegetable waste, 70% fish and 30% vegetable waste and 30% fish and 70% vegetable waste filled inside anode container at anaerobic condition and using the difference size of graphite electrodes that was 36 cm 2 and 72 cm 2 . Acrylic storage container used as the chamber structure. The proton exchange membrane uses for join the two chambers together. Microorganisms such as Shewanella used to transfer electrons directly to the anode using electrochemically. Overall 8 parameters are used will be referred to Standard Examination of Water and Wastewater by American Public Health Associate (APHA, 2002). Analysis of data was performed by using a 1-way analysis-of-variance (1-way ANOVA). The significant ANOVA (P<0.05) studies shown the different in values of the monitored 8 parameters which indicates the data obtained is accurate. The maximum voltage production can be produced with an electrode area of 72 cm 2 is 0.574 V by using 50% fish, 50% vegetable. Meanwhile for 36cm2, voltage production is 0.412 V using fish 50%, vegetable 50%. The maximum Percentage removal of COD and BOD using large electrode is 68% and 64.9%. This results indicate that MFCs are potentially effective in treating the integrated of fish and vegetable waste. The size of the electrode will affect the voltage reading because he large of surface area able to harvest more electrons compare the smaller surface area. The types of substrate also will affect the reading of the voltage because of the Population behaviors of the substrates. A lot of money and resources could be saved if the fresh market waste could be used as alternative energy.